Arabic(nanti edit) - Syed Mohd Hafiz, Syed Omar (2011)
This article ars to gather and analyze the conflicting interpretations wen by the theologians on issues related to al-Maskhu The researcher well try to elaborate various interpretebons given rn donning the meaning of al-Meskhu and than choose The strongest one. The researcher will also identify the character of the lifamsulthun as described by the Duran and explain the lessons Obtained from A This research will utilize the documentary analysis method. At the end. it is concluded that the meaning of al-Maskhu in the Cavan is the real evolution and not a metaphoncal one As for the curse that befell ashab al•Sabt. a 1.5 concluded that a is the combination of al4taskhu and avoidance from Allah's blessing. This 0 because al-Maskhu aced is the biggest temperance from Allah's blessing. As for those who obey Allah. they me be kept sway from Allah's wrath